CLASSICAL AND MODERN EXEGESIS STYLES: THE EVOLUTION OF THE DEVELOPMENT EXEGESIS STYLES FROM CLASSICAL AND MODERN PERIODS - Ahmad Zaenuri (Jurnal At-Tibyan: Jurnal Ilmu Alqur'an dan Tafsir, 2023)
This article aims to probe the discourse surrounding the debate between classical and modern interpretations of the Quran and the factors contributing to these interpretation styles' formation and evolution. The first interpretation is considered textualist and does not use much of an outside scientific approach inherited from Islam. In contrast, the modern interpretation is enunciated to depart from the traditional Islamic scholarly traditions and employ social science approaches. The research was conducted through a library research approach, analyzing classical tafsir manuscripts and modern academic research. The study extrapolated that the evolution of interpretation is shaped by the tendencies and interests of interpreters, impacted by their worldview and cultural history. As a result, the emerging interpretation styles enclose classical-literalist, theological, and modern-rationalist.